Physical Properties and Microstructure Study of Stainless Steel 316L Alloy Fabricated by Selective Laser Melting - Nurul Kamariah, Md Saiful Islam; Wan Sharuzi, Wan Harun; S. A., Che Ghani; Mohd Asnawi, Omar; Mohd Hazlen, Ramli; Muhammad Hussain, Ismail (AIP Publishing, 2017)
Selective Laser Melting (SLM) demonstrates the 21st century’s manufacturing infrastructure in which powdered raw material is melted by a high energy focused laser, and built up layer-by-layer until it forms three-dimensional metal parts. SLM process involves a variation of process parameters which affects the final material properties. 316L stainless steel compacts through the manipulation of building orientation and powder layer thickness parameters were manufactured by SLM. The effect of the manipulated parameters on the relative density and dimensional accuracy of the 316L stainless steel compacts, which were in the as-build condition, were experimented and analysed. The relationship between the microstructures and the physical properties of fabricated 316L stainless steel compacts was investigated in this study. The results revealed that 90° building orientation has higher relative density and dimensional accuracy than 0° building orientation. Building orientation was found to give more significant effect in terms of dimensional accuracy, and relative density of SLM compacts compare to build layer thickness. Nevertheless, the existence of large number and sizes of pores greatly influences the low performances of the density.